Correlation among far-infrared reflection modes, crystal structures and dielectric properties of Ba(Zn1/3Nb2/3)O3–CaTiO3 ceramics. (March 2016) - Shi, Feng; Sun, Haiqing; Liu, Hongquan; Xu, Guogang; Wang, Jing; Han, Ye
Graphical abstract: Highlights: Crystal symmetry decreases with CT concentration from cubic to hexagonal structure. Lattice constants as well as the ordered degree change with CT concentration. Ordered structures turn from 1:1 to 1:2 ordering with change of crystal structures. There is a correlation between FIR phonon modes and dielectric properties. There is a correlation between FIR phonon modes and crystal structures. Abstract: Ba(Zn1/3 Nb2/3 )O3 (BZN)–CaTiO3 (CT) microwave dielectric ceramics were synthesized at 1395 °C for 4 h using conventional solid-state sintering technique with different CT contents. The ceramics were characterized by X-ray diffraction (XRD) and far-infrared reflection (FIR) spectroscopy to evaluate correlations among crystal structures, dielectric properties, and infrared modes. XRD results showed that crystal symmetry decreased with increased CT concentration from cubic to hexagonal structure, and lattice constants and ordered degree changed accordingly. Ordered phases transformed from 1:1 to 1:2 ordered structure with crystal-structure change. FIR results demonstrated that two new IR active modes appeared at 300 cm −1, and another new mode appeared at 600 cm −1 for the x  ≥ 0.60 sample, which agreed with the change in crystal structures as confirmed by XRD results. Correlations between FIR modes and dielectric properties were established.